Connecting the World for a Shared Future: Firmly Safeguarding Stable and Smooth Global Industrial and Supply Chains - Hongbin, Ren (Napredak, 2024)
Contributing to global economic recovery, development and prosperity, the China Council for the Promotion of International Trade has made a platform of networked industrial and supply chains. In a strategic orientation towards joint prevention of shocks in the world market, as well as towards interactive development of new technology and energy, the author encourages the business community to assume a more significant role in the creation of a new market environment. This paper is aimed at pointing to the openness and cooperation of Chinese economy as an important driving force of development and progress. Inclusiveness and sustainability are a guarantee for joint prosperity, whereas the perspective is being sought in China’s further political, economic and cultural opening and connecting more strongly with the global business community